1996
DOI: 10.1042/bj3140903
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of glucose metabolism for regulation of glucose transporter type 2 (GLUT2) gene expression in liver

Abstract: Previous studies have shown that glucose increases the glucose transporter (GLUT2) mRNA expression in the liver in vivo and in vitro. Here we report an analysis of the effects of glucose metabolism on GLUT2 gene expression. GLUT2 mRNA accumulation by glucose was not due to stabilization of its transcript but rather was a direct effect on gene transcription. A proximal fragment of the 5' regulatory region of the mouse GLUT2 gene linked to a reporter gene was transiently transfected into liver GLUT2-expressing c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
78
1
1

Year Published

1997
1997
2007
2007

Publication Types

Select...
2
2
2

Relationship

1
5

Authors

Journals

citations
Cited by 102 publications
(91 citation statements)
references
References 39 publications
9
78
1
1
Order By: Relevance
“…In contrast, in GLUT 2-expressing cells, the amplitude of the glucose responsiveness of the L-PK mRNA expression was correlated with the GLUT 2 mRNA level. It should be observed that GLUT 2 mRNA accumulation is itself dependent on glucose, as previously demonstrated in hepatocytes and mhAT3F cells (3,28,29), whereas abundance of GLUT 1 mRNA was independent of glucose ( Fig. 5).…”
Section: Correlation Between Glut 2 Mrna Level and Glucose Responsivementioning
confidence: 68%
See 4 more Smart Citations
“…In contrast, in GLUT 2-expressing cells, the amplitude of the glucose responsiveness of the L-PK mRNA expression was correlated with the GLUT 2 mRNA level. It should be observed that GLUT 2 mRNA accumulation is itself dependent on glucose, as previously demonstrated in hepatocytes and mhAT3F cells (3,28,29), whereas abundance of GLUT 1 mRNA was independent of glucose ( Fig. 5).…”
Section: Correlation Between Glut 2 Mrna Level and Glucose Responsivementioning
confidence: 68%
“…In the mhPKTf3 cell line, GLUT 1 immunofluorescence was easily detectable at the plasma membrane of the cells while no 3 A. Vandewalle, unpublished results.…”
Section: Forced Expression Of Glut 2 But Not Of Glut 1 Glucose Transpmentioning
confidence: 99%
See 3 more Smart Citations